Application of electrochemical impedance spectroscopy to commercial Li-ion cells: A review - Meddings, Nina; Heinrich, Marco; Overney, Frédéric; Lee, Jong-Sook; Ruiz, Vanesa; Napolitano, Emilio; Seitz, Steffen; Hinds, Gareth; Raccichini, Rinaldo; Gaberšček, Miran; Park, Juyeon (Journal of power sources, 2020)
Electrochemical impedance spectroscopy (EIS) is a widely applied non-destructive method of characterisation of Li-ion batteries. Despite its ease of application, there are inherent challenges in ensuring the quality and reproducibility of the measurement, as well as reliable interpretation and validation of impedance data. Here, we present a focus review summarising best metrological practice in the application of EIS to commercial Li-ion cells. State-of-the-art methods of EIS interpretation and validation are also reported and examined to highlight the benefits and drawbacks of the technique. [Display omitted] •Comprehensive evaluation of EIS-based techniques for investigation of commercial LIBs.•In-depth report and analysis of a large number of papers dealing with commercial LIBs.•Critical assessment of the state-of-the-art for EIS calibration and measurement.•Critical assessment of the state-of-the-art for EIS interpretation and validation.•Critical review of both standard and new, physics-based equivalent circuit models.